Obesity is associated with a higher Torque Teno viral load compared to leanness - Herz, Carsten T.; Kulterer, Oana C.; Kulifaj, Dorian; Gelas, Fanny; Franzke, Bernhard; Haupenthal, Frederik; Prager, Gerhard; Langer, Felix B.; Marculescu, Rodrig; Haug, Alexander R.; Kiefer, Florian W.; Bond, Gregor (Frontiers in Endocrinology, 2022)
Introduction: Obesity affects a rising proportion of the population and is an important risk factor for unfavorable outcomes in viral disease including severe acute respiratory syndrome coronavirus 2- (SARS-CoV-2) associated diseases. Torque Teno virus (TTV) is a ubiquitous and apathogenic virus which reflects the immune function of its host. The aim of this study was to investigate the association between obesity and TTV load - an indirect marker of compromised viral immune response. Methods: TTV was quantified by TTV R-GENE® PCR in a total of 89 participants of which 30 were lean (BMI <25 kg/m2) and 59 were obese (BMI >30 kg/m2). For 38 subjects, follow-up was available after bariatric surgery. Results: TTV load was higher in individuals with obesity (median 2.39, IQR: 1.69–3.33 vs. 1.88, IQR 1.08–2.43 log10 copies/mL; p = 0.027). Multivariable linear modeling revealed an independent association between TTV load and obesity. TTV was positively correlated with waist-to-hip ratio and inversely with 25OH vitamin D levels. Interleukin 6 and fasting insulin resistance were confounders of the association between TTV and obesity, while age was an effect modifier. TTV load increased by 87% (95% CI 2–243) in the year following bariatric surgery. Discussion: A higher TTV load in obese individuals may reflect compromised immune function and thus might serve for risk stratification of unfavorable outcomes during infectious disease, including coronavirus disease 2019, in this population. Our data warrant further analysis of TTV-based risk assessment in obese individuals in the context of infectious disease-associated outcomes.